Modeling and analysis of filtration processes in oil reservoirs of small fields by reserves - Zhanat Alisheva; Ahmed N. AL-Dujaili; Nurbol Tileuberdi; Samal Muratova; Elmira Omirzakova; Miras Sanatbekov; Olzhas Kurmanbayev; Manat Alzhigitova (Scientific Reports)
Abstract This study focuses on modeling and analyzing filtration processes in oil reservoirs of small fields, using the Northern Karamandybas field as a case study. It examines the geological and physico-chemical characteristics of the oil-bearing reservoirs and presents a hydrodynamic model developed for the J-VII, J-VIII, and J-IX horizons. The model is built upon PVT analysis of oil, gas chromatography of dissolved gas, and incorporates detailed reservoir properties, oil characteristics, and the geological structure of productive formations. A key novelty of this research is the integration of geostatistical methods, history-matching techniques, and permeability distribution analysis to evaluate the efficiency of water injection in a highly heterogeneous reservoir. Unlike previous studies that rely solely on deterministic models, this study employs a data-driven approach that accounts for geological uncertainties, ensuring more reliable reservoir performance predictions. The adaptive water injection strategy optimizes injection rates based on real-time permeability variations, filling a critical gap in understanding the impact of heterogeneity on waterflooding efficiency. The modeling results demonstrate that water injection enhances production efficiency by maintaining reservoir pressure, improving oil displacement, and minimizing water-cut, thereby reducing development costs for reservoirs. The integration of stochastic modeling and historical data calibration ensures a balanced approach to reservoir management, improving forecasting accuracy. This research provides a foundation for further studies and practical recommendations for the optimal development of small, geologically complex oil fields.